Optimization of carvacrol, rosmarinic, oleanolic and ursolic acid extraction from oregano herbs (Origanum onites L., Origanum vulgare spp. hirtum and Origanum vulgare L.) - Baranauskaitė, Justė; Jakštas, Valdas; Ivanauskas, Liudas; Kopustinskienė, Dalia M; Drakšienė, Gailutė; Masteikova, Ruta; Bernatonienė, Jurga (Natural product research, 2016)
The aim of our study was to increase the extraction efficiency of carvacrol, rosmarinic, oleanolic and ursolic acid from the different species of oregano herbs (Origanum onites L., Origanum vulgare spp. hirtum and Origanum vulgare L.). Various extraction methods (ultrasound-assisted, heat-reflux, continuous stirring, maceration, percolation) and extraction conditions (different solvent, material:solvent ratio, extraction temperature, extraction time) were used, and the active substances were determined by HPLC. The lowest content of carvacrol, rosmarinic, oleanolic and ursolic acid was obtained by percolation. During heat-reflux extraction, the content of active substances depended on the solvent used: ethanol/non-aqueous solvent (glycerol or propylene glycol) mixture was more effective compared with ethanol alone. The results showed that for each species of oregano the most optimal extraction method should be selected to maximize the content of biologically active substances in the extracts.
Keywords: carvacrol; cinnamáty; Cymenes; rozpouštědla; kyselina ursolová; Oleanolic Acid; rosmarinic acid; extraction; cymeny; Molecular Structure; HPLC; oleanolic acid; Triterpenes; monoterpeny; dobromysl (rod); Cinnamates; Depsides; Chromatography, High Pressure Liquid; Origanum; triterpeny; Rosmarinic Acid; depsidy; Solvents; vysokoúčinná kapalinová chromatografie; ursolic acid; rostlinné extrakty; Plant Extracts; Ursolic Acid; kyselina olenalová; kyselina rozmarýnová; molekulární struktura; Monoterpenes